Real-Time monitoring of biopharmaceutical crystallization: chord length distribution to crystal size distribution for lysozyme, rHu insulin, and vitamin B12 - Pandit, A.; Katkar, V.; Ranade, V.; Bhambure, R. (Industrial and Engineering Chemistry Research, 2018)
This investigation is focused on designing an effective strategy for the real-time monitoring of biopharmaceutical crystallization using focused beam reflectance measurement (FBRM). Lysozyme, rHu insulin, and vitamin B12 were selected as model biopharmaceutical molecules for the study. Under selected experimental conditions, lysozyme exhibits polymorphism with tetragonal and needle-shaped crystals, rHu insulin forms rhombohedral crystals, and vitamin B12 forms polyhedral-shaped crystals. Focused beam reflectance measurements were performed to obtain the real time chord length distribution (CLD) of crystals obtained using static and dynamic conditions. Mathematical models were developed for converting CLD data obtained using FBRM measurements into the useful crystal size distribution (CSD) data for low (tetragonal, rhombohedral and polyhedral) and high aspect ratio crystals (needle). For high-aspect-ratio crystals, both width-based and length-based models were developed for capturing the CSD. The model validation was performed by comparing the model CSD with the CSD obtained using microscopic image analysis. Developed models effectively capture the CSD for variable shape crystals of lysozyme, rHu insulin, and vitamin B12. It was demonstrated that in the case of high-aspect-ratio crystals, there is an intrinsic limitation in using FBRM for length-based crystal size measurement.